2007
DOI: 10.1080/09548980701642277
|View full text |Cite
|
Sign up to set email alerts
|

Local statistics of retinal optic flow for self-motion through natural sceneries

Abstract: Image analysis in the visual system is well adapted to the statistics of natural scenes. Investigations of natural image statistics have so far mainly focused on static features. The present study is dedicated to the measurement and the analysis of the statistics of optic flow generated on the retina during locomotion through natural environments. Natural locomotion includes bouncing and swaying of the head and eye movement reflexes that stabilize gaze onto interesting objects in the scene while walking. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…The most similar work to ours also uses the Brown range image database to generate realistic synthetic flow fields (Calow et al, 2004). The authors use a gaze tracker to record how people view the range images and then simulate their motion into the scene with varying fixation points.…”
Section: Previous Workmentioning
confidence: 98%
See 1 more Smart Citation
“…The most similar work to ours also uses the Brown range image database to generate realistic synthetic flow fields (Calow et al, 2004). The authors use a gaze tracker to record how people view the range images and then simulate their motion into the scene with varying fixation points.…”
Section: Previous Workmentioning
confidence: 98%
“…Optical flow has been generated from range images by Calow et al (2004), but they focus on a synthetic model of human gaze and ego-motion. Unlike (Calow et al, 2004), we focus on optical flow fields as they arise in machine vision applications as opposed to human vision. 2 The range image database we use captures information about surfaces and surface boundaries in natural scenes, but it is completely static.…”
Section: Obtaining Training Datamentioning
confidence: 99%
“…(10) gives us expressions for the retinal speed [21,22] and stereo disparity [23,24] as a function of depth. Suppose an observer is translating laterally at a velocity T x ms −1 and uses a head and /or eye movement to track a point at depth z 0 .…”
Section: A Theoretical Model: Frontoparallel Disksmentioning
confidence: 99%
“…The latter found that deeper objects within a volume tend to be darker, which may be related to the proximity-luminance bias in human vision. Natural scene range data have been used for generating models of image statistics such as the optical flow seen by a moving observer [21,22] and the retinal disparities for a binocular observer [23,24].…”
Section: Related Workmentioning
confidence: 99%
“…The incremental enhancement of our models with changes in the relative influence of receptive field segments supports the view that MSTd is optimized for optic flow direction selectivity (Duffy and Wurtz 1995;Lappe et al 1996) independent of other motion parameters (Calow and Lappe 2007). This selectivity may be the result of the dynamic adjustment of weightings on the inputs to each neuron (Wang 1995), possibly through Hebbian shaping guided by heading direction feedback (Zhang et al 1993).…”
Section: Gain Modulation By Optic Flowmentioning
confidence: 67%